A case study in US urban leadership the incumbency of Milwaukee Mayor Henry Maier - Gruberg, Martin
Henry Maier, former Milwaukee mayor, was called a great figure, a senior liberal urban statesman and a master politician. He was also called unbalanced, unpredictable and goofy. This work looks at the career of a man who made himself into a political institution.